KARAKTERISASI PHARSIAL ISOLATBAKTERI PENDEGRADASI PHENOL DARI TABLET BAKTERI - T. Sembiring; A. Susilorukmi (Jurnal Kimia Terapan Indonesia, 1999)
An aerobic pure culture (18) was isolated from the tablet of mixed culture bacteria which is originated from a farm land. The gram positive isolate able to degrade phenol about 550 mg/l.d. Morphology of the isolate changes with the culture ages. it was in rod shape during the logarithmic growth phase and changes to the o valform during the stationary phase. The range of temprature growth is 27-34°C and the optimum temprature of the isolate is 30°C with doubling time about 7 hours. Substrate could be utilized by the isolate are alcohol, aromatic compound and carbohydrate. Methanol, ethanol, isopropanol (each 10%; v/v), 4-Chlor phenol (0.2 mM), 4-nitrophenol(0.25 mM), anniline (1 mM)  and glucose are some substrate has been tested for the bacterial growing. Salt (NaCl) tolerance for the isolate is up to 2% (v/v) and the addition of ammonium salt would be support the bacterial growthKey words:Bacterial tablet, aerobic, phenol degradation, 4-chlor phenol, 4-nitro phenol, anniline, glucose, methanol, ethanol, iso-propanol, isolation, partial characterization.